Memorable Tourist Experience and its Impact on Tourist Engagement - Syahbudiman, Rayhan; Hendrayati, Heny; Kusumah, Ahmad Hudaiby Galih; Marimon, Frederic; Marhadi, Marhadi (Image : Jurnal Riset Manajemen, 2024)
This research aims to analyze the influence of memorable tourist experiences on tourist engagement among tourists visiting glamping destinations in Bandung and West Bandung Districts. The research methods used are descriptive and verificative. The data were collected by distributing questionnaires to 107 domestic tourists who had previously been guests at glamping sites in Bandung and West Bandung Districts. Convenience sampling was used as the sampling technique. The data analysis technique employed classical assumption tests and simple regression analysis. The research results indicate that memorable tourist experiences have a positive and significant influence on tourist engagement. Creating memorable experiences is crucial for destination managers to enhance tourist engagement. Memorable experiences tend to lead to higher levels of tourist involvement with the destination. This research provides theoretical implications for understanding the relationship between memorable tourist experiences and tourist engagement, as well as practical implications for destination management.